2020
DOI: 10.22373/ekw.v6i2.5383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Soil Actinomycetes From Malino Pine Forest Rhizosphere of South Sulawesi

Abstract: Actinomycetes are a group of Gram-positive bacteria that produce active compounds with a wide distribution range in nature especially in soil. The purpose of this study was to isolate actinomycetes from the rhizosphere soil of the Malino pine forest, South Sulawesi. This research is a descriptive qualitative study of 15 actinomycetes isolated from the rhizosphere soil of the Pine Forest. These 15 isolates have been successfully identified to the genus level. Actinomycetes were isolated by direct dilution metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Husnah et al (2012) succeeded in obtaining 24 isolates of soil actinobacteria from the Pocut Meurah Intan Forest Park, Aceh Besar. Sukmawaty et al (2020) succeeded in isolating 15 isolates of actinobacteria from the soil of the Malindo pine forest, South Sulawesi. Kanti (2005) reported 31 isolates from the Jambi National Forest Park.…”
Section: Results Of Actinobacterial Isolatesmentioning
confidence: 99%
“…Husnah et al (2012) succeeded in obtaining 24 isolates of soil actinobacteria from the Pocut Meurah Intan Forest Park, Aceh Besar. Sukmawaty et al (2020) succeeded in isolating 15 isolates of actinobacteria from the soil of the Malindo pine forest, South Sulawesi. Kanti (2005) reported 31 isolates from the Jambi National Forest Park.…”
Section: Results Of Actinobacterial Isolatesmentioning
confidence: 99%
“…The Two soil samples was collected from agricultural fields and dumping site for actinomycetes isolation and 30 actinomycetes colonies were isolated. Sukmawaty et al 20 reported the 15 actinomycetes colonies isolated from the soil of Malindo pine forest, South Sulawesi. MMD1 able to produce higher zone of hydrolysis (36 mm) of endoglucanase compare with the Lenni et al 21 reported the zone of hydrolysis 2.93 mm of endoglucanase by streptomyces spp.…”
Section: S T R E Pto My Ce S a L O N G W I T H O T H E Rmentioning
confidence: 99%